Correlates in granting students loans in Uganda: - Muweesi, Charles; Shizhou, Lou; Muwagga, Mugagga Anthony; Cuiying, Wang; Ssali, Kizza Francis; Tomusange, Robert; Mugenyi, Kuteesa Disan; Namagero, Tendo Shira (Academic Journals, 2022)
This mixed research study focused on the selection criterion and guidelines used by the Higher Education Students Financing Board (HESFB) in granting students loan scheme to University Students in Uganda with a sample from Makerere University. Findings revealed that the majority of the loan beneficiaries are aware of these guidelines and one to benefit from the scheme had to formally pass A level education stage with 3 principle passes in a science subjects combination and are selected after filling a standard application form. Although many come from low economic family status with heavy household poverty, the study concluded that the selection criteria favors students who have passed science subjects and thus leaving behind impoverished students from humanity study disciplines/courses. Thus it recommends a framework for the need to revise the guidelines to cater and consider all backgrounds of applicants for this loan scheme irrespective of their course, family background and economic status to achieve the program goal as it's done in other countries. Key words: Loan scheme guidelines, Higher Education Students Education Financing Board (HESFEB policy program, financing higher education.
Thematic selection criterion and guidelines
Aritcle